2009
DOI: 10.5539/ijbm.v4n9p170
|View full text |Cite
|
Sign up to set email alerts
|

Rebranding of Higher Educational Institutions in Malaysia

Abstract: In order to create reputations in the local and international market, rebranding of Malaysian Higher Educational Institutions (HEIs) have been practiced intensively in the recent years. The main objective of this study is to review rebranding of HEIs in Malaysia, which are focus more on public and private HEIs. In order to adapt education to national development needs and as the number of enrolment of tertiary students has been increasing rapidly, education reforms are constantly taking place in Malaysia. In r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
(2 reference statements)
0
12
0
5
Order By: Relevance
“…In 2006, the Government of India released its first Integrated Energy Policy (IEP) (GoI, 2006). The broad vision behind the IEP is to meet reliably the demand for energy services with safe and convenient energy at the least cost in a technically efficient, economically viable and environmentally sustainable manner.…”
Section: Integrated Energy Policymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, the Government of India released its first Integrated Energy Policy (IEP) (GoI, 2006). The broad vision behind the IEP is to meet reliably the demand for energy services with safe and convenient energy at the least cost in a technically efficient, economically viable and environmentally sustainable manner.…”
Section: Integrated Energy Policymentioning
confidence: 99%
“…It results in an installed nuclear capacity in India of 216 GW in 2050, more than 10% of the global nuclear capacity of 2 000 GW in this scenario. The Indian nuclear capacity figure for 2050 lies between the optimistic (275 GW) and the pessimistic (208 GW) scenarios in the IEP report of the Indian government (GoI, 2006). It is also assumed that the feasible hydro potential of almost 150 GW in India can be exploited to a large degree by 2050.…”
Section: Scenario Variants For the Indian Power Sectormentioning
confidence: 99%
“…The Malaysian governments has also been working closely with overseas partners, (including multinational corporations) to set up branch campuses, twining programs namely '2+1' or '1+2', meaning that first digit for study of local college and second digit for study with overseas twining university and establishing foreign campuses (Goi, 2009). Study shows that 19 UK universities and 18 Australian universities are currently operating 110 and 71 twinning program in Malaysia respectively (MOK, 2011).…”
Section: Joint-degree Programmentioning
confidence: 99%
“…For every season with yield loss, we multiplied the percentage of loss by the proxy for the market price of wheat, set at the Bihar government minimum support prices for 2012/13, which was 0.81 PPP$/kg. 56 Method to calculate CO 2 fertilisation Long-term experiments have revealed that an increase in atmospheric CO 2 has a positive impact on yield for some crops. [57][58][59][60] We assume 0.028 per cent increase in wheat yields with a 1 ppm increase of CO 2 in the atmosphere.…”
Section: The Geneva Papers On Risk and Insurance-issues And Practicementioning
confidence: 99%